Income, Expenses and Expenditure Patterns of Elementary Public-School Teachers: Inputs to a Proposed Financial Literacy Program - Generose C. Fernando; Gilbert S. Arrieta (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2023)
This study explored the income, expenses, and expenditure patterns of eight elementary public school teachers from urban areas. Using the case study method, it compared and analyzed teacher’s expenses before and during these times when financial distress hit the world, the COVID-19 pandemic. The results showed that most teachers tend to borrow more than what they were earning from different lending institutions. They engaged in different lending or pawning schemes in order to address their financial needs. Based on the findings, it can be concluded that the participants are financially challenged and continuously struggle to make both ends meet. A financial literacy program focusing on management of funds/resources, financial decision-making proficiency, planning, savings and investing, and financial responsibility was developed that can be provided to teachers. It is recommended that school heads may look into these financial concerns and a financial literacy program be integrated in in-service trainings.